Kekosongan Norma Pengaturan Valuasi Hak Kekayaan Intelektual Sebagai Aset Dalam Sistem Hukum Indonesia. - Putu Eka Trisna Dewi; Putu Chandra Kinandana Kayuan; Dedy Suryana; Ni Made Rai Sukardi; Padi Razaz (INVENTION: Journal of Intellectual Property Law, 2026)
This study aims to examine the normative gap in the regulation of Intellectual Property (IP) valuation as an asset within the Indonesian legal system. As an intangible asset, Intellectual Property possesses significant economic value and has increasingly been recognized as an asset that can be utilized in business activities and financing schemes, including as collateral. However, Indonesia currently lacks comprehensive legal provisions governing the standards, methods, and mechanisms for the valuation of Intellectual Property. This research employs a normative legal research method using statutory and conceptual approaches. The findings reveal that the existing legal framework does not provide adequate legal certainty regarding the valuation process of Intellectual Property, particularly concerning valuation standards and the institutions authorized to conduct such valuations. This condition creates various obstacles to the utilization of Intellectual Property as an economic asset, especially in legal relationships involving creditors and debtors. Therefore, this study recommends the establishment of a clearer, more integrated, and comprehensive regulatory framework on Intellectual Property valuation to ensure legal certainty and support the optimal utilization of Intellectual Property as a valuable economic asset.